Analysis of the Influence of Entrepreneurial Skills and Learning Behavior of Managers on Village-Owned Enterprise Innovation in the Special Region of Yogyakarta - Gatot Ferianto; Entoh Tohani; Sulasmi (JURNAL ECONOMINA, 2026)
This study aims to analyze the influence of entrepreneurial skills and learning behavior of managers on BUMDes innovation in the Special Region of Yogyakarta. The study employed a quantitative approach with a survey method. The study population comprised 35 BUMDes operating in the Yogyakarta Special Region (DIY) using a proportional random sampling technique. Data were collected through a questionnaire. The instrument's validity was confirmed with a Pearson product-moment correlation of 0.611. The reliability test, with a Cronbach's Alpha value of 0.809, demonstrated excellent reliability. Multiple linear regression was used to analyze the partial and simultaneous effects of entrepreneurial skills, learning behavior, and BUMDes innovation. The results of the study indicate that: (1) entrepreneurial skills have a positive and significant effect on BUMDes innovation; (2) management learning behavior also has a positive and significant effect on innovation; and (3) both variables simultaneously make a strong contribution to increasing BUMDes innovation. These findings confirm that human resource capacity, particularly entrepreneurial skills and an adaptive learning culture, are key factors in driving institutional innovation and village-based business development.